Effect of Maturity and Storage Temperature on Shelf-Life and Quality of Banana Cv. Grand Naine - A P Gonge (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
A study was undertaken at Regional Horticulture Research Station, NAU, Navsari, during 2008-2009 to assess the effect of maturity stage and storage temperature on shelf-life and quality of banana cv. Grand Naine. The experiment was evaluated in Completely Randomized Ddesign based on the factorial concept, and comprised of three maturity stages (75, 90 and 100% maturity) and four storage temperatures (12°C, 14°C, 16°C&ambient temperature). Fruits harvested at 75% maturity and stored at 12°C recorded maximum green-life and better overall shelf-life, whereas, yellow-life was highest when fruits at 75% maturity were stored at 14°C. Best colour and texture was seen in fruits harvested at 100% maturity and stored at 16°C.